Cruel summer - Brubaker, Ed (Image Comics, 2022)
"In the summer of '88, Teeg Lawless comes home to plan the biggest heist of his career. But Teeg's son Ricky and his friends are starting down the same dark path their fathers are on, and this is about to become the worst summer of their lives" --Amazon.